Clonidine in Hyperactive, Mentally Retarded Children - J Gordon Millichap (Pediatric Neurology Briefs)
The effects of oral clonidine on hyperactive children with comorbid mental retardation were examined in 10 children (mean age 7.6 years) treated at the Department of Psychiatry, King George’s Medical College, Lucknow, India.